Educação inclusiva: aspectos históricos, políticos e ideológicos da sua constituição no cenário internacional - de Souza Barbosa, Daniella; Machado Fiuza Fialho, Lia; dos Santos Machado, Charliton José (Universidad de Costa Rica, 2018)
The ethical imperative that guarantees human rights and equality for people with disabilities through Inclusive Education is a relatively recent paradigm in Brazilian scenario and its implementation is complex. The objective is to develop a historical, documentary-type research, a path on international public policies of Special Education with emphasis on paradigmatic changes emerging chronologically in Brazil. It is concluded that the eighteenth and nineteenth centuries were marked by the homogenizing segregation of people with disabilities in special schools and that, from the twentieth century onwards; special classes emerged, driven by international documents. Such classes were overcome the current ideology of equality and social inclusion towards the differences that make possible not only the inclusion in the regular school, but some mechanisms to fight for equality of conditions. The reflections show that the international discussions and agreements impel Brazil to align its internal policy towards the guarantee of human rights and equality for people with disabilities.